2019
DOI: 10.3390/s19163624
|View full text |Cite
|
Sign up to set email alerts
|

Application and Optimization of Wavelet Transform Filter for North-Seeking Gyroscope Sensor Exposed to Vibration

Abstract: Conventional wavelet transform (WT) filters have less effect on de-noising and correction of a north-seeking gyroscope sensor exposed to vibration, since the optimal wavelet decomposed level for de-noising is difficult to determine. To solve this problem, this paper proposes an optimized WT filter which is suited to the magnetic levitation gyroscope (GAT). The proposed method was tested on an equivalent mock-up network of the tunnels associated with the Hong Kong‒Zhuhai‒Macau Bridge. The gyro-observed signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The selection of the mother wavelet is dependent on the properties of the wavelet and its similarity with collected signals. In this study, Symlets 6 (Sym6) mother wavelet was selected because it can reduce the phase distortion in signal analysis and reconstruction [44], and it is suitable for the characteristics of GNSS measurements [24]. Figure 1a illustrates the scaling and function of the Sym6 wavelet.…”
Section: Methodsmentioning
confidence: 99%
“…The selection of the mother wavelet is dependent on the properties of the wavelet and its similarity with collected signals. In this study, Symlets 6 (Sym6) mother wavelet was selected because it can reduce the phase distortion in signal analysis and reconstruction [44], and it is suitable for the characteristics of GNSS measurements [24]. Figure 1a illustrates the scaling and function of the Sym6 wavelet.…”
Section: Methodsmentioning
confidence: 99%
“…The gyro total station (gyro-theodolite), which integrates the gyroscope and total station (theodolite), is a precise and sensitive measurement and directional instrument that can independently determine true north azimuths in underground spaces where satellite signals are hardly received [1,2]. Recently, it has been widely used to orient tunnel breakthroughs, mining, subway construction, missile launching, weapons guidance, etc [3][4][5]. The processing of the observed gyroscope signal is one of the main elements controlling the accuracy and precision of the gyro total station [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors influence the quality of gyroscope signals. Previous studies have suggested that the gyroscope signal is not only affected by the error of the sensor itself, but also by external environmental factors, such as ground vibration, wind vibration, electromagnetic interference, temperature, and air pressure changes [3,4,[7][8][9][10]. Some of these factors result in the periodic characteristics of the gyro signal, which decreases the accuracy of the instrument [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al. applied the optimized WT filter to the magnetic levitation gyroscope (GAT) and successfully reduced the vibration noise in actual use [ 17 ]. The WT method can effectively reduce the random noise in FOG signal, but this method needs to preset wavelet basis function and decomposition level, so the adaptability is not good.…”
Section: Introductionmentioning
confidence: 99%